Automatic Cable Cutter and Roller with Arduino - Ahmad, Akram; Ishak, Maizul (Progress in Engineering Application and Technology, 2022)
When it comes to the installation of any electrical or electronic device, then cables and wiring form “nerves” to carry electric currents or pulses. Electrical engineering does not necessarily include electronic engineering. Therefore, this field is sometimes known as “electrical and electronic engineering”. During the wiring, process of cable cutting and winding is a basic thing that happens throughout the work. By building a prototype such as "Automatic Cable Cutter and Roller with Arduino", it provides convenience to users in doing work and even save working time. This prototype was equipped with two combined circuits that can work at the same time. Arduino was a mainstay component to supervise and control the entire cutter circuit. The cutting circuit part uses 2 power supplies. The first supply was for Arduino Nano which was 5v. The second supply was 12v and was connected to the motor driver as a stepper motor power supply. The use of 2 stepper motors was intended as a feeder and cutter. The feeder motor work as the cable supplier to the cutter motor. This circuit runs after length and cable quantity set. Next is the roller & puller circuit. This circuit was supplied with 12v. The usage of a power window motor was very useful with high traction and moderate movement. The circuit work as a tool to wind and pull the cable in case it gets stuck on something during wiring. In conclusion, the prototype "Automatic Cable Cutter and Roller with Arduino" can provide a convenience in electrical and electronic wiring work.